Analisis Efektivitas Project-based Learning Dalam Meningkatkan Keterampilan Berpikir Kritis Siswa - Irfan (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study aims to analyze the effectiveness of Project-based Learning (PjBL) in improving students' critical thinking skills. The method used is a narrative review study, which examines various studies related to the impact of PjBL on critical thinking skills at various levels of education. A literature search was conducted using keywords such as "project-based learning," "critical thinking skills," and "students" through online databases, focusing on articles published in the last five years. The results of the study indicate that PjBL has a positive impact on improving critical thinking skills, especially in terms of analysis and problem solving. Project design that is relevant to students' real lives, sufficient implementation duration, and active support from educators are factors that influence the success of PjBL implementation. Although PjBL is considered effective, the results vary, especially at the elementary education level, where the project design needs to be adjusted to students' cognitive development. This study suggests that the implementation of PjBL be further considered at various levels of education, by considering contextual factors and educator readiness in implementing this method. In addition, training for educators to design and implement effective PjBL is urgently needed. This study provides practical recommendations for educators and policy makers.